Evapotranspiration to minimise acid mine decant from a decommissioned colliery - Haagner, ASH; van Wyk, SJ (Mine Closure 2023: Proceedings of the 16th International Conference on Mine Closure, 2023)
Acidic mine water decant from legacy coal mines presents significant environmental impacts to the Highveld watercourses in South Africa. The costs and logistics for active treatment are often not feasible due to the remoteness of sites, excessive capital and operational costs, lack of infrastructure and complications with brine and sludge disposal. The regulatory authorities currently prefer active pumping and desalinating water from flooded underground compartments, followed by the discharge of treated water into natural watercourses. However, if a sufficient body of monitoring evidence can prove efficacy with a high degree of confidence, then lower-cost and more sustainable water management alternatives may become a reality. In this project we monitored different tree plantation trial blocks of two species that were established in 2012 to reduce vertical groundwater recharge from rainfall that would report to underground workings. Reducing the ingress rates to below critical levels would eliminate the decant of acidic mine water to receiving watercourses. Monitoring focussed on establishing water budgets (rainfall, throughfall, soil moisture and moisture extinction, sap flow and groundwater levels) via continuous logging instruments. The monitoring period was four years, from 2018 to 2022, once the trees were nearing maturity. The data were used in building a conceptual site model and then a geohydrological model to estimate draw-down within the trial blocks. A site survey for possible plantation expansion areas followed, after which the geohydrological model was again updated to extend the ingress reduction to a larger area. The study found that trees survived very well, but that different species were better suited to specific conditions. Water uptake and ingress reduction were very effective in all but the highest rainfall periods. The geohydrological model showed effective draw-down, with the expansion model confirming that the trees could limit vertical groundwater recharge to near zero. However, a residual interflow from deeper aquifers would still result in some recharge to underground workings. During periods of excessive rainfall, this would have to be pumped and used to irrigate plantations to prevent decant altogether. The establishment of commercial-scale forestry plantations with continuous-cover harvesting could fulfil an important role for local enterprise development, job creation and effective sustainable post-mining land-use, whilst contributing significantly to continuous passive groundwater decontamination, reducing groundwater liability and environmental degradation.
Keywords: evapotranspiration